2000
DOI: 10.1046/j.1365-2036.2000.00833.x
|View full text |Cite
|
Sign up to set email alerts
|

Third line treatment for Helicobacter pylori: a prospective, culture‐guided study in peptic ulcer patients

Abstract: Background: A third line treatment is needed in roughly 5% of patients infected with Helicobacter pylori. Few data have been reported on efficacy of treatment regimens in these patients. Methods: A prospective trial was designed to study the effectiveness of third line treatment of H. pylori infection in ulcer patients. Two‐week quadruple, culture‐guided, combinations were used in 31 consecutive patients. Susceptibility to metronidazole and clarithromycin were studied by E‐test, and thereafter a predetermined … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
76
1
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(79 citation statements)
references
References 12 publications
1
76
1
1
Order By: Relevance
“…However, even knowing the susceptibility of H. pylori, eradication rates do not achieve 100%. 19 The search for alternative antibiotics to overcome the problem on non-response is still ongoing. Rifabutin is an antitubercolotic compound which has been used, reaching interesting eradication rates ranging from 71 to 86.6%.…”
Section: Discussionmentioning
confidence: 99%
“…However, even knowing the susceptibility of H. pylori, eradication rates do not achieve 100%. 19 The search for alternative antibiotics to overcome the problem on non-response is still ongoing. Rifabutin is an antitubercolotic compound which has been used, reaching interesting eradication rates ranging from 71 to 86.6%.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, a variable proportion of non-eradicated patients is made of subjects who harbor strains sensitive to the administered drugs, and in these patients the reasons for treatment failure are unclear [139] . For example, Gomollón et al [140] reported how third-line treatment often (in 50% of the cases) failed to eradicate H pylori infection, in spite of giving a 14-d, full-dose, quadruple culture-guided combination, showing that in vitro susceptibility did not predict eradication success. In the same way, Vicente et al [141] determined the effectiveness of a third, cultureguided, treatment of H pylori infection after two unsuccessful attempts.…”
Section: Is It Necessary To Performmentioning
confidence: 99%
“…Zullo et al [76] reported 83% cure rate in patients who had previously failed two courses of clarithromycin-amoxicillin and clarithromycin-tinidazole based triple therapies. Gomollón et al [140] studied the effectiveness of third-line treatment of H pylori infection with two-week quadruple, culture-guided regimens. The combination of omeprazole, tetracycline, bismuth and clarithromycin showed an eradication rate of only 36%, but if amoxicillin was used the rate was 67%.…”
Section: Consecutive Eradication Treatmentsmentioning
confidence: 99%
See 1 more Smart Citation
“…9 While culture and susceptibility tests are sensitive in refractory patients, the results observed in vivo are often disappointing when tailored to reflect in vitro susceptibility to standard antiHelicobacter antibiotics. 10 Gastroenterologists and microbiologists continue the search for new therapies due to the increasing number of target subjects for H. pylori and to the physiological and pharmacoeconomic burden of a second course of therapy. 11,12 Bovine lactoferrin (bLf) is a single polypeptide chain glycoprotein of the transferrin family weighing between 75 000 and 80 000 Da.…”
Section: Introductionmentioning
confidence: 99%